Data Security using Partially Transmitted Sequences and Fast Fourier Transform - Dohare, Prateek Kumar; Ahirwar, Preeti (International Journal of Computer Sciences and Engineering, 2025)
Data security can be achieved in a variety of ways. Often encryption algorithms are prone to attacks and hence can’t ensure high data security for classified and highly confidential data, the reason being the fact that encrypted data is often perceptible and hence more prone to attacks due to its existence on the application layer level of the OSI model. Hence the necessity for physical layer security arises. The proposed technique uses partially transmitted sequences along with the fast Fourier transform for physical layer security. The performance of the proposed system is based on the complementary cumulative distribution function (CCDF) of the crest factor of the data. It has been shown that the proposed system attains a low crest factor therefore reducing the perceptibility and increasing the level of security.